Metafunctional signifying elements in Angkola ceremonial discourse: A Systemic Functional Linguistic analysis - Ilham Sahdi Lubis; Nurlela Nurlela; T. Silvana Sinar; Eddy Setia (Universitas Syiah Kuala, 2026)
This study aimed to describe the realization of metafunctional meanings, the organization of the lexicogrammatical system, and the enactment of social context in the Angkola ceremonial discourse within the framework of Systemic Functional Linguistics (SFL). Specifically, the study focused on identifying metafunctional meaning-forming elements, explaining the structural organization of Angkola lexicogrammar, and examining how social context was linguistically realized. A qualitative research design was employed to achieve these objectives. The data were collected from audio-recordings, document analysis, interviews, participant observation, direct observation, and introspection. The data were analyzed interactively and continuously until the analysis reached saturation. The findings revealed that all metafunctional meaning-forming elements were realized in the Angkola ceremonial discourse, and each element played a role in clarifying the functional meanings of words within the analyzed clauses. Experiential meaning was realized through Process, Participant, and Circumstantial elements; Interpersonal meaning was realized through Mood and Residue; and Textual meaning was realized through Theme and Rheme. The Theme element was further classified into Marked Topical Theme and Unmarked Topical Theme. These findings contributed to the documentation and linguistic understanding of local languages, supporting sustainable linguistic knowledge development and inclusive learning practices. The study implied that SFL-based analysis can be effectively applied to regional languages to enrich linguistics education, preserve linguistic diversity, and strengthen language-based pedagogical materials.